PYROMETER - Bansal, Shivam; Vashiath, Yogesh; Batra, Ujjwal (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
A pyrometer is a type of thermometer used to measure high temperatures. Various forms of pyrometers have historically existed. In the modern usage, it is a noncontacting device that intercepts and measures thermal radiation, a process known as pyrometry. The thermal radiation can be used to determine the temperature of an object’s surface. The word pyrometer comes from the Greek word for fire, "πυρ" (pyro), and meter, meaning to measure. The word pyrometer was originally coined to denote a device capable of measuring the temperature of an object by its incandescence, or the light that is emitted by the body as caused by its high temperature You can feel a fire some distance away because it gives off heat radiation in all directions. In theory, if the fire behaves exactly according to the laws of physics, the radiation it produces is related to its temperature in a very predictable way. So if you can measure the radiation, you can precisely measure the temperature even if you’re standing some way off. That’s the theory behind a pyrometer: a very accurate kind of thermometer that measures something’s temperature from the heat radiation it gives out. IJRDO